2021
DOI: 10.3389/fevo.2021.645727
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in Florida, United States: A Case Study of Quantification and Characterization With Intertidal Snails

Abstract: Concentrations of microplastics are increasing within the oceans, including waters surrounding Florida, United States. Miles of sandy beaches make the sunshine state a prime tourist destination leading to an increased amount of pollution along Florida coasts. Microplastics can cause damage to intertidal organisms, as well as causing issues up the food chain with biomagnification and seafood consumers, such as humans. Florida is also subject to hurricanes which often distribute sediments, filling the water colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 66 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…For example, microfibers were the dominant type of MP in both the water and bivalves analyzed (97% and 93%) [59]. However, within the bivalves, microfragments made up a larger proportion of observed microplastics (7% present in bivalves vs. 3% in water) [59]. This may be due to their tendency to settle at a higher rate within water than microfibers [60].…”
Section: Dominant Mp Typesmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, microfibers were the dominant type of MP in both the water and bivalves analyzed (97% and 93%) [59]. However, within the bivalves, microfragments made up a larger proportion of observed microplastics (7% present in bivalves vs. 3% in water) [59]. This may be due to their tendency to settle at a higher rate within water than microfibers [60].…”
Section: Dominant Mp Typesmentioning
confidence: 97%
“…In recent bioaccumulation studies, they were found less than microfibers. For example, microfibers were the dominant type of MP in both the water and bivalves analyzed (97% and 93%) [59]. However, within the bivalves, microfragments made up a larger proportion of observed microplastics (7% present in bivalves vs. 3% in water) [59].…”
Section: Dominant Mp Typesmentioning
confidence: 99%